Traditional spices of Dayak Kenyah society in East Kalimantan - SITI SUSIARTI; FRANCISCA MURTI SETYOWATI (Society for Indonesian Biodiversity, 2005)
The diversity of plant in Indonesia is high, including variety of spices, which have been known by Indonesian society since long time ago. Several very popular plants are clove (Syzygium aromaticum), pepper (Piper nigrum), cinnamon (Cinnamomum burmanii), and nutmeg (Myristica fragrans). Variety of spices has connection with cultures. In each region and society, they have a special spices in their traditional food. The research was conducted in villages in Pujungan district and other places in East Kalimantan Province and commonly Dayak Kenyah society. The methods used for this study was by interviewing of local society and direct observation in the fields where plant spices occurred. The results indicated that traditional Dayak in East Kalimantan used bekai (Albertisia papuana Becc.), payang aka (Hodgsonia macrocarpa (Bl.) Cogn.), payang kurek (Aleurites moluccana (L.) Willd.), payang kayu (Pangium edule Reinw.), payang lengu (Ricinus communis L.), and payang salap (Sumbaviopsis albicans (Blume) J.J.Sm.) for preparing their food with certain method.Key words: traditional spices, Dayak Kenyah, East Kalimantan.